Farfield pattern and guided-mode extraction analysis for highly directional emission from photonic-crystal based AlGaInP/InGaP MQW color-converters in thin-film geometry - Amade Ndiaye; Hai Son Nguyen; Christian Seassal; Emmanuel Drouard; Badhise Ben Bakir (AIP Advances, 2022)
This paper provides novel design guidelines for highly directional emission from PhC-based AlGaInP/InGaP MQW color converters (CC) in a thin-film geometry through an in-depth analysis of the measured azimuthal and spectrally resolved farfield emission patterns and a modal analysis based on coupled-mode theory and a herein-developed model for quantifying the spontaneous emission distribution between guided modes. The fabricated CC can exhibit directionality up to ∼5 times higher than that of Lambertian emitters close to normal incidence. We believe that all the novel insights set through our analyses help in properly controlling the emission directionality from photonic-crystal-based MQW CC at the display level, which would eliminate the need for additional external optics. This could pave the way for the use of MQW CC to achieve compact full-color microdisplays on a single wafer.